COMPREHENSIVE REVIEW ON INTEGRATION OF SUPPORT PERSONNEL IN HEALTHCARE - 1Khairat Hassan Mahdi Khairat, 2Salem Saleh M Alyami, 3Wedad Ali MarzooqAlyami, 4Nouf Ali MarzooqAlyami, 5Saleh Abdullah Saleh Alyami, 6Rizq Mohammed Rizq Al ishaq, 7SALEH Hussain S Alyami, 8Mohammed Ali Mohammed Majrashi (Chelonian Research Foundation, 2022)
This comprehensive review examines the integration of support personnel in healthcare, exploring its implications, challenges, and potential benefits. Historically, healthcare has advanced from the space of specialists and medical caretakers to incorporate an assortment of support staff, including nurture colleagues, doctors, and partnered well-being experts. Integration of support staff is fundamental to extending productivity, making strides to care, moving forward with quiet involvement, and encouraging collaboration. Be that as it may, challenges such as usage issues, preparation needs, and administrative issues remain. Best practices and advancements such as collaborative care models, collaborative learning, innovation arrangements, and proficient improvement offer ways to illuminate these issues. Future bearings incorporate extending parts and duties, tending to staff deficiencies, utilizing innovation and information examination, and supporting arrangement change. Healthcare organizations can increase worker efficiency by utilizing collaborative collaboration and engaging in advancement. This is often good for everyone. Keywords: Integration, support personnel, healthcare, interdisciplinary collaboration, challenges, best practices, innovations, future directions.